Analysis Of The Application Of Financial Accounting Standards Of Entities Without Accountability Public At The Cooperative Of Employees Of The Republic Of Indonesia - Catur Kumala Dewi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Financial reports are formal reports of the financial activities of an entity including cooperatives and are prepared as a management responsibility to internal and external parties. Generally Accepted Accounting Standards are still difficult for cooperatives to apply because existing standards are more specific to large entities and have public accountability. IAI has issued Standard Financial Accounting for an entity without Public Accountability or known as SAK ETAP. SAK ETAP is intended to accommodate the needs of an entity that has significantly no accountability to operate on a Small and Medium Enterprises (UKM) and cooperative basis. This study aims to evaluate the implementation of SAK ETAP in the Financial Report of KPRI Padangsidimpuan City. KPRI Padangsidimpuan City is a cooperative engaged in the savings and loan sector. The research method is descriptive comparative by comparing primary and secondary data. It was found that the cooperative's financial reports in 2021 did not comply with the SAK ETAP principles and several reports had not been presented such as the Cash Flow report and Report of changes in equity. This is due to the limited accounting skills acquired by its human resources.